New proposals for the international classification of diseases-11 revision of pain diagnoses - Rief, Winfried; Treede, Rolf-Detlef (The journal of pain, 2012)
The representation of pain diagnoses in current classification systems like International Classification of Diseases (ICD)-10 and Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV does not adequately reflect the state of the art of pain research, and does not sufficiently support the clinical management and research programs for pain conditions. Moreover, there is an urgent need to harmonize classification of pain syndromes of special expert groups (eg, International Classification of Headache Disorders) and general classification systems (eg, ICD-11, DSM-V). Therefore, this paper summarizes new developments, and proposals for pain diagnoses in revised classification systems. A qualitative review of the literature concerning new proposals for classification of pain syndromes that are based on consensus groups was conducted. Selected proposals of national and international pain societies that are based on consensual processes are presented. These proposals can be condensed to be used in ICD-11 classification. The benefits of considering multidimensional and transdiagnostic processes for the classification process are also outlined. The manuscript provides options how to transform current pain-specific classification proposals to the revision of ICD-11. Perspective Pain research and expertise must be more visible in the ICD-11 revision process. A general category for pain diagnoses as well as specific pain diagnoses under existing categories of organ-specific sections are needed.
Available online 2 April 2012
Gesehen am 21.06.2018